Species delimitations in the Atractus collaris complex (Serpentes: Dipsadidae) - Passos, Paulo; Prudente, Ana L. C.; Ramos, Luciana O.; Caicedo-Portilla, José Rances; Lynch, John D. (Zootaxa, 2018)
We reassessed the taxonomic status of the species in the Atractus collaris complex (A. alphonsehogei, A. collaris, A. limitaneus, and A. gaigeae) on the basis of congruence between quantitative and qualitative morphological characters (meristic, morphometric, color pattern, hemipenis, and scale microdematoglyphics) along its wide geographical distribution. Our results support the recognition of three species with apparently fixed diagnostic characters. We propose the synonymization of Atractus limitaneus with A. collaris based on the wide overlap of all morphological character systems here analyzed, as well as on the basis of examination of the holotype and two topotypes of A. limitaneus. Finally, we discuss the geographical variation and morphological distinction of A. alphonsehogei, A. collaris and A. gaigeae. Furthermore, we provide a dichotomous key for all recognized species in the A. collaris species group.